Differential Expression of Woodchuck Toll-Like Receptors 1–10 in Distinct Forms of Infection and Stages of Hepatitis in Experimental Hepatitis B Virus Infection - Williams, John Bradley; Hüppner, Alena; Mulrooney-Cousins, Patricia M.; Michalak, Tomasz I. (Frontiers in Microbiology, 2018)
Woodchucks infected with woodchuck hepatitis virus (WHV) represent a highly valuable model of human hepatitis B virus (HBV) infection, chronic hepatitis (CH), and virus induced-primary liver cancer. Toll-like receptors (TLRs) are important mediators of immune responses playing pivotal roles in the pathogenesis of viral diseases; however, their expression profiles in different forms of infection and stages of hepatitis, and in healthy animals remain essentially unknown. In this study, woodchuck TLRs 1-10 exon fragments were identified and TLR genes transcription quantified in livers, primary hepatocytes, peripheral blood mononuclear cells (PBMC), and in selected organs during experimental WHV infection. Among others, liver biopsies from acute hepatitis (AH) and CH showed significantly augmented expression of the majority of TLRs when compared to healthy and woodchucks prior to AH, with resolved AH or primary occult infection. In contrast to the liver tissue, significant upregulation of TLR3, TLR4 and TLR10, but downregulation of TLR7, characterized hepatocytes derived from livers of animals with resolved AH accompanied by secondary occult infection. Hepatocytes from CH showed significantly lower expression or a trend toward suppression of several TLRs when compared to hepatocytes from healthy animals and woodchucks with other forms of infection or hepatitis, suggesting that hepatocyte innate immune response is downregulated during CH. Contrastingly, upregulated transcription of some TLRs characterized PBMC throughout CH. Our study uncovered that TLR expression significantly varies between different forms of hepadnaviral infection and whether infection is accompanied or not by hepatitis. The results also showed that the profiles of TLRs’ expression in circulating lymphomononuclear cells do not mirror those of livers and hepatocytes from infected animals. These findings are of importance to the understanding of immune process operating at different sites targeted by virus in the course of hepadnaviral infection and evaluation of future therapies modifying antiviral innate responses in the woodchuck model.